MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS ANAK BERKEBUTUHAN KHUSUS MELALUI FLASHCARDS DI SEKOLAH KHUSUS NEGERI 03 JAKARTA PUSAT - Amelia, Siska (STAI Darul Qalam Tangerang, 2021)
This jurnal was aimed at knowing whether students’ vocabulary mastery could be improved by using Flashcards in the class X of The State Owned Special School 03 of Central Jakarta. In addition, this study is also aimed at describing how the implementation of Flashcards in improving students’ Vocabulary Mastery for Students with Special Needs. This study is categorized as the Classroom Action Research (CAR) method in which to identify and to solve the problem on students’ vocabulary mastery. It is initiated through the interview the teacher and through the observation in the class X at the State Owned Special School 03 of Central Jakarta; considered as the class whose English score are very low. The amount of students in that class is 6. In this classroom action research, the writer implements the Kurt Lewin’s design which consists of four phases. Those are planning, acting, observing, and reflecting. Meanwhile, the data is derived among from the test (pretest and posttest), interview, and observation. Therefore, this study is included into quantitative descriptive research